KARAKTERISTIK PASIEN PENYAKIT JANTUNG BAWAAN DI RUMAH SAKIT JANTUNG PEMBULUH DARAH NASIONAL HARAPAN KITA PERIODE TAHUN 2019–2023 - Abednego, Nathaniel; Situmorang, Desman; Setiabudi, Edwin; Lelya, Olfi; Prakoso, Radityo (Universitas Kristen Maranatha, 2026)
Congenital heart disease (CHD) is one of the most common congenital disorders, affecting approximately 8 per 1,000 live births in Indonesia. This study aimed to describe the demographic and clinical characteristics of pediatric patients with CHD treated at Rumah Sakit Jantung dan Pembuluh Darah Harapan Kita from 2019 to 2023. A descriptive cross-sectional study was conducted using medical record data from 5,599 patients under the age of 18. Variables analyzed included annual case distribution, demographic characteristics, CHD classification, complications, and treatment outcomes. The highest number of cases was recorded in 2023 (1,457 cases; 26.02%). Most patients were under five years old (59.94%), with a slight female predominance (50.94%). Acyanotic CHD was more prevalent (60.33%), predominantly ventricular septal defect (53.11%), while cyanotic CHD accounted for 39.67%, dominated by Tetralogy of Fallot (59.70%). Congestive heart failure and pulmonary hypertension were the most frequent complications. Cyanotic CHD was associated with growth and developmental disorders and malnutrition, whereas acyanotic CHD generally demonstrated adequate nutritional status. The most common intervention was total repair of Tetralogy of Fallot. Surgical success rates were high in acyanotic (97.37%) and cyanotic CHD (94.73%). Mortality was higher in cyanotic CHD, particularly with delayed diagnosis. Early detection improves outcomes significantly overall.